Modeling the global trade and environmental impacts of biofuel policies - Bouët, Antoine; Valin, Hugo; Dimaranan, Betina (International Food Policy Research Institute, 2010)
There is rising skepticism about the potential positive environmental impacts of first generation biofuels. Growing biofuel crops could induce diversion of other crops dedicated to food and feed needs. The relocation of production could increase deforestation and bring significant new volumes of carbon into the atmosphere. In this paper, we develop a methodology for assessing the indirect land use change effects related to biofuel policies in a computable general equilibrium framework. We rely on the trade policy model MIRAGE and on the GTAP 7 database, both of which have been modified and improved to explicitly capture the role of different types of biofuel feedstock crops, energy demand and substitution, and carbon emissions. Land use changes are represented at the level of agroecological zones in a dynamic framework using land substitution with nesting of constant elasticity of transformation functions and a land supply module that takes into account the effects of economic land expansion. In this integrated global approach, we capture the environmental cost of different land conversions due to biofuels in the carbon budget, taking into account both direct and indirect carbon dioxide emissions related to land use change. We apply this methodology to look at the impacts of biofuel (ethanol) policies for transportation in the United States and in the European Union with and without ethanol trade liberalization. We find that emissions released because of ethanol programs significantly worsen the total carbon balance of biofuel policies. Ethanol trade liberalization benefits are ambiguous and depend highly on the parameters governing land use change, particularly in Brazil. We conclude by pointing out the critical aspects that have to be refined in order to improve our understanding of the environmental implications of biofuel development.